The psychological attraction of food brand by football player’s Advertisement: A Research study of consumer behavior towards product Choice - Zhi-Lin Liu; Supat Chupradit; Priyanut Wutti Chupradit; Abdul Qadus; Abdelmohsen A. Nassani; Mohamed Haffar (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This research study measures psychological attraction in relation to food brands by football player’s advertisements. This research is based on consumer behavior and examines the effect of product choices—and has been conducted in the context of China using primary data analysis techniques. For analysis, the data is generated on the basis of responses to specific questions related to the psychological attraction, food brand advertisement, consumer behavior, and product choice. To measure the data, the smart PLS software ran different results such as statistical ratio analysis, T-test analysis, regression analysis, generalized linear model, and that reliability test analysis. This study aimed to better understand the components of product attributes in the sporting environment in order to better understand what makes a product-athlete endorsement connection more effective. While it is usual for businesses to utilize athletes for advertising and marketing their products or services, only a limited number of studies have looked at the qualities of athletes and the roles these characteristics play in developing an effective advertisement relationship. Analysis of data findings shows that psychological attraction has a positive and significant impact on consumer behavior and product choice. On the other hand, food brand advertisement shows a positive but insignificant effect on product choice.